Alirocumab for the treatment of hypercholesterolemia. (4th May 2017) - Tomlinson, Brian; Hu, Miao; Zhang, Yuzhen; Chan, Paul; Liu, Zhong-Min
ABSTRACT: Introduction : Alirocumab is a human monoclonal antibody inhibiting proprotein convertase subtilisin/kexin type 9 (PCSK9) that is administered by subcutaneous injection every 2 weeks. Area covered : Herein, the authors discuss the background to inhibition of PCSK9 and the pharmacodynamics, pharmacokinetics and clinical trials with alirocumab. Alirocumab produces substantial reductions in low density lipoprotein cholesterol (LDL-C) in patients with and without background statin treatment. The safety profile appears very promising from the relatively short term studies that have been completed but there are some remaining concerns about long term risks of neurocognitive events and developing diabetes. Expert opinion : The profound reduction in LDL-C with alirocumab is most likely to translate into cardiovascular benefits in the ODYSSEY OUTCOMES trial and is unlikely in itself to result in any major adverse effects. The high cost and the current lack of long-term safety and efficacy data will restrict the use of alirocumab to patients who have high cardiovascular risk from established atherosclerotic cardiovascular disease or heterozygous familial hypercholesterolemia and who are unable to achieve LDL-C targets with maximally tolerated dose of statins with or without other lipid-lowering drugs. When further data become available, these indications are likely to be expanded.